Geologic legacy spanning >90 years explains unique Yellowstone hot spring geochemistry and biodiversity - Devon Payne; Eric C. Dunham; Elizabeth Mohr; Isaac Miller; Adrienne Arnold; Reece Erickson; Elizabeth M. Fones; Melody R. Lindsay; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2019)
Summary Little is known about how the geological history of an environment shapes its physical and chemical properties and how these, in turn, influence the assembly of communities. Evening primrose (EP), a moderately acidic hot spring (pH 5.6, 77.4°C) in Yellowstone National Park (YNP), has undergone dramatic physicochemical change linked to seismic activity. Here, we show that this legacy of geologic change led to the development of an unusual sulphur‐rich, anoxic chemical environment that supports a unique archaeal‐dominated and anaerobic microbial community. Metagenomic sequencing and informatics analyses reveal that >96% of this community is supported by dissimilatory reduction or disproportionation of inorganic sulphur compounds, including a novel, deeply diverging sulphate‐reducing thaumarchaeote. When compared to other YNP metagenomes, the inferred functions of EP populations were like those from sulphur‐rich acidic springs, suggesting that sulphur may overprint the predominant influence of pH on the composition of hydrothermal communities. Together, these observations indicate that the dynamic geological history of EP underpins its unique geochemistry and biodiversity, emphasizing the need to consider the legacy of geologic change when describing processes that shape the assembly of communities.